1977
DOI: 10.1677/joe.0.0740001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oestradiol on the Metabolism of Androgens by Human Prostatic Tissue

Abstract: The uptake and metabolism of testosterone, androstenedione and 5alpha-dihydrotestosterone (DHT) by human benign hyperplastic prostates and prostatic carcinomas have been measured in organ culture. DHT was a major metabolite of both testosterone and androstenedione in the benign tissue and the androstanediols were the principal metabolites of DHT. Over half the carcinomas produced less DHT from testosterone than the benign hyperplastic prostates, and carcinomas from the oldest patients showed an enhancement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Similar studies performed by Bard & Lasnitzki (1977) have shown that oestradiol is capable of decreasing the formation of DHT from testosterone. The higher mean level of tissue oestradiol in cancerous tissue than in hypertrophie tissue and its negative correlation with tissue concentrations of DHT and 5a-androstane-3a,17ß-diol in patients with BPH could also imply that this oestrogen exerts some actions on the regulation of the two main enzymes, i.e.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar studies performed by Bard & Lasnitzki (1977) have shown that oestradiol is capable of decreasing the formation of DHT from testosterone. The higher mean level of tissue oestradiol in cancerous tissue than in hypertrophie tissue and its negative correlation with tissue concentrations of DHT and 5a-androstane-3a,17ß-diol in patients with BPH could also imply that this oestrogen exerts some actions on the regulation of the two main enzymes, i.e.…”
Section: Discussionsupporting
confidence: 69%
“…However,we have found that in benign tissues, DHT and androstanediols are the main metabolites of testosterone, whereas androstenedione represents the major metabolite in neoplastic tissue (Ghanadian, Masters & Smith, 1979). Furthermore, oestradiol has been shown in vitro to inhibit the activities of 5a-reductase (Shimazaki, Kurihara, Ito & Shida, 1965) and the 3a(ß)-hydroxysteroid dehydrogenase in BPH and neoplastic tissues (Jenkins & McCaffery, 1974;Tan, Antonipillai & Murphy, 1974;Bard & Lasnitzki, 1977). All these investigations emphasize the significance of the combined effects of androgen metabolites and oestradiol in the prostate.…”
Section: Introductionmentioning
confidence: 97%
“…This observation strongly suggests that there was an estrogen-dependent positive regulation of the ARC as reported earlier for the canine prostate [ 19,201. Alternatively, it is also pos-Androgen receptor. sible that estrogens act either via hypophyseal-gonadal axis leading to low levels of plasma testosterone [21,22] or by suppressing the production of dihydrotestosterone from testosterone [23] so that the ARC depletion rate is reduced or stopped. Our results on the PCA group are in apparent contrast with those of Ekman et al [24] and Concolino et al [25] who have found nearly 80% of the patients to be ARC positive, even though they did not receive any hormone therapy.…”
Section: Discussion Steroid Receptorsmentioning
confidence: 99%
“…In contrast, poorly differentiated prostatic neoplasms were markedly deficient in their capacity to convert testosterone to Sa-DHT. Bard & Lasnitzki (1977) found on the other hand, no relationship between androgen metabolism and the degree of differentiation of the carcinoma. In their study, prostatic carcinoma produced less Sa-DHT from testosterone than the benign hyperplastic prostate in agreement with the reports of Prout et al (1976) and Djoeseland et al (1977).…”
Section: Discussionmentioning
confidence: 82%